Optimization Of Positive Self-Concept Among Students of School Affected By The Drought Disaster - Utami, Dyah Rahmawatie Ratna Budi; Nurrohmah, Anjar; Hermawan, Danang (CV. Rayyan Dwi Bharata, 2026)
Adolescence is a transitional period between childhood and adulthood with various accompanying turmoil. Adolescents are also vulnerable to mental health problems and negative influences from the surrounding environment, including living conditions affected by disasters. SMPN 3 Miri is located in Gilirejo Baru Village, an area affected by drought. Drought disrupts the family economy, parents moving to find work raises anxiety for adolescents regarding the continuity of their education and health. The problems at SMPN 3 Miri are the limitations of students in developing a positive self-concept to face existing challenges, as well as the absence of educational media regarding strengthening positive self-concept in an effort to improve adolescent mental health. Improving children's mental health can be done by optimizing positive self-concept. The implementation of education includes analyzing adolescent needs, media preparation, and a socialization process. Self-love education is carried out through initial apperception, material presentation, discussion and sharing tips on self-love techniques using several media such as PPT, videos, and leaflets. The results of this community service are an increase in knowledge by 44% and attitudes by 48.3% regarding positive self-concept in adolescents. Other outputs include leaflets, community service videos, and scientific articles published in accredited national journals.